Post-transcriptional Modulation of Iron Homeostasis during p53-dependent Growth Arrest - Zhang, Fan (American Society for Biochemistry and Molecular Biology, 2008)
Iron plays an essential role in cell proliferation and is a required cofactor for a number of critical cellular enzymes. In this report we investigate changes in proteins of iron metabolism during p53-mediated replicative arrest. Following the induction of p53 in H1299 lung cancer cells containing a doxycycline-inducible p53, an increase in both H and L subunits of ferritin protein was observed. To determine the mechanism of this effect, we investigated the ability of p53 to regulate ferritin. Real time reverse transcription-PCR demonstrated no difference in levels of ferritin H mRNA in the presence and absence of p53. Because these results suggested that transcriptional mechanisms were not responsible for the p53-dependent increase in ferritin, we tested whether a post-transcriptional mechanism was involved. RNA bandshift assays revealed that induction of p53 decreased iron regulatory protein binding. Consistent with this observation, Western blot analysis revealed a decline in transferrin receptor 1 protein levels following induction of p53. Collectively, these results suggest that p53 may induce cell cycle arrest not only by well described mechanisms involving the induction of cyclin-dependent kinase inhibitors but also by the recruitment of pathways that reduce the availability of intracellular iron.